Study of visual evoked potentials in the assessment of the central optic pathways in leprosy patients - Ulvi, H; Yigiter, R; Yoldas, T; Erdem, I; Müngen, B (Springer-Verlag Italia Srl, 2003)
We evaluated the possible involvement of central optic pathways (COP) in leprosy patients with visual evoked potentials, an easy, sensitive and reliable noninvasive method for evaluation of COP. In 37 patients with lepromatous leprosy and in 37 age-matched controls, we measured reversal pattern visual evoked potentials (RP-VEP) and nerve conduction parameters. The mean latency value of positive peak P100 in leprosy patients was significantly delayed compared to that of controls (patients, 108.02+/-9.61 ms in left eye and 108.23+/-8.51 ms in right eye; controls, 96.22+/-4.20 ms in left eye and 95.75+/-4.03 ms in right eye; p<0.05). Abnormally delayed P100 latency was recorded in 5 of 37 leprosy patients (13.5%). The mean amplitude of P100 latency in leprosy patients was smaller than that of controls (patients, 8.7+/-5.6 muV in left eye and 9.5+/-4.8 muV in right eye; controls, 10.7+/-4.6 muV in left eye and 10.5+/-5.1 muV in right eye), but this difference was not significant. No correlation was observed between abnormalities of RP-VEP and sensorimotor nerve conduction parameters. This study suggests that involvement of COP may develop in patients with lepromatous leprosy. RP-VEP measurement, which can be easily and rapidly performed in an EMG laboratory using standard equipment, can show these alterations.
Keywords: leprosy; central optic pathways; visual evoked potentials